A starch edible surface coating delays banana fruit ripening. (February 2019) - Thakur, Rahul; Pristijono, Penta; Bowyer, Michael; Singh, Sukhvinder P.; Scarlett, Christopher J.; Stathopoulos, Costas E.; Vuong, Quan V.
Abstract: A rice starch edible coating blended with sucrose esters was developed for controlling the postharvest physiological activity of Cavendish banana to extend postharvest quality during ripening at 20 ± 2 °C. Coating effectiveness was assessed against changes in fruit physiochemical parameters such as weight loss, titratable acidity, total soluble solids, flesh fruit firmness, ion leakage, colour change, respiration, ethylene production, chlorophyll degradation and starch conversion were determined. The topography of coating material on the fruit surface was evaluated by scanning electron microscope (SEM). Surface morphology studies highlighted the binding compatibility of the coating matrix with the fruit peel character and formed a continuous uniform layer over the fruit surface. The results showed that the coating was effective in delaying ethylene biosynthesis and reducing respiration rate. Other factors impacting included delayed chlorophyll degradation, reduced weight loss and retention of fruit firmness for the first six days, all of which improved the commercial value of the fruit. The shelf life of coated fruit was prolonged for 12 days in comparison with the untreated control which ripened within seven days and lost marketability after Day 6. The pilot study demonstrates the effectiveness of a starch-based edible coating formulation for improving the ambient storage capacity of banana fruit. Highlights: A rice starch-ι-carrageenan coating blended with sucrose ester was developed. A 40% extension in the postharvest life was recorded at room temperature (20 °C). Coating delayed the ethylene production and starch degradation rate during storage. The treatment reduced the fruit weight loss, firmness and chlorophyll degradation of banana fruit.